2017
DOI: 10.1186/s13047-017-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical diagnosis of symptomatic forefoot neuroma in the general population: a Delphi consensus study

Abstract: BackgroundThere is limited evidence for defining what specific method or methods should be used to clinically influence clinical decision making for forefoot neuroma. The aim of this study was to develop a clinical assessment protocol that has agreed expert consensus for the clinical diagnosis of forefoot neuroma.MethodsA four-round Delphi consensus study was completed with 16 expert health professionals from either a clinical or clinical academic background, following completion of a structured literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This number allowed for drop out at each stage. Dando [10] reported that the inclusion of a wide range of professions from a range of clinical backgrounds with a geographical diversity is good practice as it develops the participants to be a representative group [11]. A heterogenous group, with a range of stakeholders, encourages different outlooks and decision-making, which in turn enriches the data leading to better outcomes of credibility and acceptability [12].…”
Section: Methodsmentioning
confidence: 99%
“…This number allowed for drop out at each stage. Dando [10] reported that the inclusion of a wide range of professions from a range of clinical backgrounds with a geographical diversity is good practice as it develops the participants to be a representative group [11]. A heterogenous group, with a range of stakeholders, encourages different outlooks and decision-making, which in turn enriches the data leading to better outcomes of credibility and acceptability [12].…”
Section: Methodsmentioning
confidence: 99%
“…People with pain from a Morton’s neuroma often describe it as “like walking on a pebble,” particularly if it is worse when walking bare foot 14. It may present as paraesthesia radiating to the toes.…”
Section: What You Should Covermentioning
confidence: 99%
“…It may present as paraesthesia radiating to the toes. Neuropathic type pain, often described as “ burning” or “electric shock” sensations, may also indicate a Morton’s neuroma, particularly if it radiates into the toes 14. Neuropathic pain symptoms can also occur owing to oedema secondary to plantar plate damage or hallux rigidus 512.…”
Section: What You Should Covermentioning
confidence: 99%
See 2 more Smart Citations